Optimasi formula effervescent berbasis nanoenkapsulat Eucalyptus citriodora - Kendri Wahyuningsih; Nausika Estetia Putri Jatmiko; Rohula Utami; Sri Yuliani (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Eucalyptol (1,8-cineole) compound contained in eucalyptus oil has the potential to inhibit viral infection pathways, as an antimicrobial and as an immunoregulator. Therefore, the development of eucalyptus oil-based effervescent health drinks is urgently needed to relieve the symptoms of being infected a virus during this pandemic. However, the volatility of eucalyptus oil is quite high, so a nano-based encapsulation method is needed to slow release of these volatile compounds. This study aims to obtain the best formula for Eucalyptus citriodora oil-based effervescent granules with controlled release system in nanostructure. The experimental design used was the Taguchi method with 3 replications. The combination of level factors in the optimal formula obtained through the Taguchi loss function optimization method were effervescent materials factor-level 2, lactose/sucralose ratio factor-level 3 and nanoencapsulated/ascorbic acid ratio factor-level 2. The optimal formula was (1) effervescent materials factor: 24% sodium bicarbonate, 12% tartaric acid, 11% citric acid; (2) lactose/sucralose ratio factor: 46.2% / 0.2%; (3) nanoencapsulated/ascorbic acid ratio factor: 4.5% / 2%. The optimal product characteristics were water content of 5.52%, pH of 5.9, dissolving time of 106 seconds, carr's index of 23.56, hausner's ratio of 1.31, and total essential oil content of 0.014mL/4gram. This product can be used as a health drinks (throat lozenges) and immune booster.